2023
DOI: 10.1002/adfm.202306549
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Hybrid Perovskite/Organic Tandem White Light Emitting‐Diodes with External Quantum Efficiency Exceeding 20%

Abstract: Perovskite light‐emitting diodes (PeLEDs) have shown great potential for low‐cost display and lighting technologies, and all‐inorganic blue PeLEDs are recognized as a promising substitute for blue fluorescent/phosphorescent organic light‐emitting diodes (OLEDs) owing to their superior color purity and great stability potential. However, confined by the solution fabrication process, depositing multi‐layered white PeLEDs remains a challenge. Here, a newly designed hybrid perovskite/organic tandem white LED (POTW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…For example, a quantum dot liquid crystal TV is fabricated by applying quantum dot patterned color filters and liquid crystal display 28 , 29 , and a white light LED is prepared by combining QLEDs with OLEDs 30 . Tandem LEDs that connect two or more electroluminescence (EL) units of LEDs through a unique interconnecting layer (ICL) can offer an effective way to integrate the different technologies for better display applications 31 34 . Another important advantage of tandem devices is that the operational lifetime can be dramatically improved due to the reduced current under the same luminance, which is especially beneficial for the PeLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a quantum dot liquid crystal TV is fabricated by applying quantum dot patterned color filters and liquid crystal display 28 , 29 , and a white light LED is prepared by combining QLEDs with OLEDs 30 . Tandem LEDs that connect two or more electroluminescence (EL) units of LEDs through a unique interconnecting layer (ICL) can offer an effective way to integrate the different technologies for better display applications 31 34 . Another important advantage of tandem devices is that the operational lifetime can be dramatically improved due to the reduced current under the same luminance, which is especially beneficial for the PeLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The inset indicates the precursor material cost of representative emitters in each field [12]. [1,10,11,20,31,32,34,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. (c) Evaluation of perovskite lighting from emitters to devices to applications.…”
Section: Introductionmentioning
confidence: 99%
“…Efficiency chart of PeLEDs with (a) various colors and (b) various perovskite forms. Data was collected from[1,10,11,20,31,32,34,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. (c) Evaluation of perovskite lighting from emitters to devices to applications.…”
mentioning
confidence: 99%
“…Solution-processed organic–inorganic hybrid perovskite (OIHP) films are promising materials for use in future photovoltaic devices. The stability of OIHP films is one of the key issues to overcome compared with other competing commercial products. It has been observed that OIHP films are very sensitive to the environment conditions and can degrade quickly in the external environment such as light, temperature, etc., , decomposing into metal halides and gases .…”
Section: Introductionmentioning
confidence: 99%